REFORMASI BIROKRASI DI BADAN PUSAT STATISTIK KABUPATEN TULUNGAGUNG - Dandut Suyono; Teguh Pramono (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
BPS Tulungagung has a reasonably heavy workload, on the other hand, a limited number of human resources so that reform is needed to achieve a common goal. Generally, BPS Reformation aims to build a profile and behavior of professional BPS officials, with high integrity, and fulfilling their duties in providing excellent service on the results of quality statistical data so that data users can access statistical information faster, better, more comfortable, and cheaper. Therefore, this study analyzes the implementation of bureaucratic reform from these aspects by using a qualitative approach through in-depth interviews. In the end, this research shows that the implementation of bureaucratic reform at BPS Tulungagung requires a more effective and efficient control and incentive system.